2011
DOI: 10.1002/jssc.201100560
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer for selective extraction of 3‐methylflavone‐8‐carboxylic acid from human urine followed by its determination using zwitterionic hydrophilic interaction liquid chromatography

Abstract: A novel water-compatible molecularly imprinted SPE combined with zwitterionic hydrophilic interaction liquid chromatography method for selective extraction and determination of 3-methylflavone-8-carboxylic acid (MFA), the main active metabolite of flavoxate in human urine, was developed and validated. The effects of progenic solvents, pH, cross linker and amount of monomer were studied to optimize the efficiency and selectivity. The molecularly imprinted polymer showed good specific adsorption capacity with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Moreover, 3methylflavone-8-carboxylic acid is stated as one of the official impurities of FLV in the British Pharmacopoeia (BP) [6] and the United States Pharmacopeia (USP) [7]. For the determination of MFC, several analytical approaches have been devised, such as HPLC [6][7][8][9][10][11] and capillary electrophoresis [12] methods.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 3methylflavone-8-carboxylic acid is stated as one of the official impurities of FLV in the British Pharmacopoeia (BP) [6] and the United States Pharmacopeia (USP) [7]. For the determination of MFC, several analytical approaches have been devised, such as HPLC [6][7][8][9][10][11] and capillary electrophoresis [12] methods.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review revealed that many analytical methods such as direct [11,12,13] and derivative [14] ultraviolet-visible (UV-Vis) spectrophotometric, spectrofluorometric [15,16], high-performance liquid chromatography (HPLC) [17,18,19,20,21], ultra-performance liquid chromatography (UPLC) [22], liquid chromatography (LC)-mass spectrometry (MS) [23,24], and capillary zone electrophoresis [25,26] methods for the determination of MOX alone and in combination with other drugs in different formulations and in different biological samples. Bibliography data showed that UV-Vis spectrophotometric [27], HPLC [28,29,30,31,32,33,34], electroanalytical [35], and capillary electrophoresis methods [36] were reported for the determination of FLX alone or in combination with other drugs. Only one reversed-phase (RP)-HPLC method has been reported for the concurrent estimation of MOX and FLX in formulation [37].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Also, some HPLC methods have focused on the analysis of the active metabolite of FLV, (3-methylavone-8-carboxylic acid), in human urine. 23,24 Regarding the FLV/OFL pharmaceutical mixture, a literature review revealed few methods for the simultaneous assay of the two drugs. These methods include second derivative and absorption ratio spectrophotometric methods for the simultaneous determination of the two drugs in tablets, 25 and an HPLC method for their determination in spiked human plasma employing protein precipitation pretreatment and a gradient elution mode.…”
Section: Introductionmentioning
confidence: 99%